BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Demography of endangered juvenile green turtles in face of environmental changes: 10 years of capture-mark-recapture efforts in Martinique - Pierre Lelong; Aurélien Besnard; Marc Girondot; Caroline Habold; Fabienne Priam; Mathieu Giraudeau; Guillaume Le Loc'h; Aurélie Le Loc'h; Pascal Fournier; Christine Fournier-Chambrillon; Paco Bustamante; Sophie M. Dupont; et al. (Biological Conservation, 2024)

First look on the home range, movement, and habitat selection of the invasive Northern raccoon (Procyon lotor) in France through two contrasted populations - Manon Gautrelet; Jean-François Gerard; Rémi Helder; Pascal Fournier; Christine Fournier-Chambrillon; Pauline Hubert; Estelle Isère-Laoué; Lucille Capitaine; Maëlle Dupuy; Lucie Dispan de Floran; Clémence Alleman; Alain Devos (European Journal of Wildlife Research, 2024)

Persistent organochlorine pesticides in periprostatic adipose tissue from men with prostate cancer: Ethno-geographic variations, association with disease aggressiveness - Jean-Philippe Antignac; Sandy Figiel; Michèle Pinault; Pascal Blanchet; Franck Bruyère; Romain Mathieu; Souhil Lebdai; Georges Fournier; Jerome Rigaud; Karine Mahéo; Philippe Marchand; Ingrid Guiffard; et al. (Environmental Research, 2023)

Ecological and genomic vulnerability to climate change across native populations of Robusta coffee ( Coffea canephora ) - Rémi Tournebize; Leyli Borner; Stéphanie Manel; Christine N. Meynard; Yves Vigouroux; Dominique Crouzillat; Coralie Fournier; Mohamed Kassam; Patrick Descombes; Christine Tranchant‐Dubreuil; Hugues Parrinello; Catherine Kiwuka; et al. (Global Change Biology, 2022)
The assessment of population vulnerability under climate change is crucial for planning conservation as well as for ensuring food security. Coffea canephora is, in its native habitat, an understorey tree that is mainly distributed in the lowland rainforests of tropical Africa. Also known as Robusta, its commercial value constitutes a significant revenue for many human populations in tropical countries. Comparing ecological and genomic vulnerabilities within the species’ native range can provide valuable insights about habitat loss and the species’ adaptive potential, allowing to identify genotypes that may act as a resource for varietal improvement. By applying species distribution models, we assessed ecological vulnerability as the decrease in climatic suitability under future climatic conditions from 492 occurrences. We then quantified genomic vulnerability (or risk of maladaptation) as the allelic composition change required to keep pace with predicted climate change. Genomic vulnerability was estimated from genomic environmental correlations throughout the native range. Suitable habitat was predicted to diminish to half its size by 2050, with populations near coastlines and around the Congo River being the most vulnerable. Whole‐genome sequencing revealed 165 candidate SNPs associated with climatic adaptation in C. canephora , which were located in genes involved in plant response to biotic and abiotic stressors. Genomic vulnerability was higher for populations in West Africa and in the region at the border between DRC and Uganda. Despite an overall low correlation between genomic and ecological vulnerability at broad scale, these two components of vulnerability overlap spatially in ways that may become damaging. Genomic vulnerability was estimated to be 23% higher in populations where habitat will be lost in 2050 compared to regions where habitat will remain suitable. These results highlight how ecological and genomic vulnerabilities are relevant when planning on how to cope with climate change regarding an economically important species.

REview of potentially inappropriate MEDIcation pr[e]scribing in Seniors (REMEDI[e]S): French implicit and explicit criteria - Barbara Roux; Julie Berthou-Contreras; Jean-Baptiste Beuscart; Marion Charenton-Blavignac; Jean Doucet; Jean-Pascal Fournier; Blandine de la Gastine; Sophie Gautier; Régis Gonthier; Valérie Gras; Muriel Grau; Pernelle Noize; et al. (European Journal of Clinical Pharmacology, 2021)

Suitability of patient education materials on proton-pump inhibitors deprescribing: a focused review - Jérôme Nguyen-Soenen; Cédric Rat; Jean-Pascal Fournier (European Journal of Clinical Pharmacology, 2020)

Tracing historical introductions in the Mediterranean Basin: the success story of the common genet (Genetta genetta) in Europe - Philippe Gaubert; Irene Del Cerro; Alejandro Centeno-Cuadros; Francisco Palomares; Pascal Fournier; Carlos Fonseca; Jean-Paul Paillat; José Antonio Godoy (Biological Invasions, 2015)

Non-steroidal anti-inflammatory drugs (NSAIDs) and hypertension treatment intensification: a population-based cohort study - Jean-Pascal Fournier; Agnès Sommet; Robert Bourrel; Stéphane Oustric; Atul Pathak; Maryse Lapeyre-Mestre; Jean-Louis Montastruc (European Journal of Clinical Pharmacology, 2012)

Electrophysiological characterization of three non-synonymous single nucleotide polymorphisms (R87Q, A251T, and P307S) found in hKv1.5 - Isabelle Plante; Dominique Fournier; Guylaine Ricard; Benoît Drolet; Gilles O’Hara; Jean Champagne; Patrick Mathieu; Richard Baillot; Pascal Daleau (Pflügers Archiv - European Journal of Physiology, 2006)

Cut-off phenomenon in the protective effect of alcohols against lysophosphatidylcholine-induced calcium overload - Louis-Jean Bordeleau; Laimonis Gailis; Dominique Fournier; Marc Morissette; Thérèse Di Paolo; Pascal Daleau (Pflügers Archiv - European Journal of Physiology, 2005)